The effect of wood chip surface depth on peak force during impacts - Lee-Confer, Jonathan (Frontiers in Environmental Health, 2025)
ObjectivePlaygrounds are essential for children's physical, social, and mental health. However, only 4.7% of playgrounds meet safety standards for wood chip surface depth around playground structures. This study aimed to quantify peak force attenuation at safety-compliant (9-inch) vs. non-compliant (5-inch) wood chip depths.MethodsWood chip layers of 5 inches and 9 inches were placed on a calibrated force platform. A 4.54-kg medicine ball was dropped from a consistent height onto the wood chips, and peak forces and time to peak force were measured.ResultsThe 9-inch wood chip layer significantly reduced peak forces compared to the 5-inch layer, showing a 44% reduction (p < 0.001). No significant differences were observed in time to peak force between the two conditions (p = 0.46).DiscussionCompliant wood chip surface depths reduce impact forces substantially, emphasizing the importance of routine inspection and maintenance of playground surfaces to safety standards. This practice can help minimize injuries in children resulting from playground falls.